Regional culture: The role of the invisible hand in shaping local family firms’ top management team - Yu, Xiaodong; Zhang, Yuyin; Cheng, Xirong; Li, Huan; Chen, Yujie; Zhou, Weizhong (Frontiers in Psychology, 2022)
Research on family businesses has focused on the differences between family and non-family firms regarding the top management team (TMT), while this study further explores the difference within family firms from different regional culture based on the perspective of socio-emotional wealth (SEW) and evolutionary psychology. Using a sample comprised of all 625 family firms listed on the Small & Medium Enterprise Board and Growth Enterprise Board in Shenzhen Stock Exchange, this study finds that in regions of strong clan culture, family members are more willing to be involved in a family business and accept lower economic rewards. Particularly, when financial risk is high, these relationships mentioned above become more significant. Based on the results, this study proves that regional culture can affect the characteristics of top management teams in family firms, explains the heterogeneity of family firms’ decision-making from a culture-based perspective and extends existing research on family business from the level of “family firm vs. non-family firm” to that of “family firms affected by different regional cultures”.